BUNGA SEBAGAI OBJEK RITUS PERIBADATAN HINDU DI BALI : BUNGA SEBAGAI OBJEK RITUS PERIBADATAN HINDU DI BALI - Panji Tresna, I Gusti Ngurah Agung; I Made Gede Nesa Saputra (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Humans' inability to understand God in metaphysical form often gives rise to the need to use symbolic or representational means in an effort to understand or describe a sublime and unattainable existence, one of which is a vital object as a symbol of God for the Balinese Hindu community is the existence of flowers in Every offering is considered as a condition that increases aesthetic passion or a condition within the spirit of human relationship with God of Flowers in Hindu religious practices in Bali. The research uses qualitative methods with a descriptive approach used to analyze and describe data from literature studies, strengthening understanding about the presence of flowers in rituals. The results of the research are divided into three discussion points (1) The Significance of Flowers in Hindu Religious Rites in Bali (2) Flowers as a Medium of Offerings (3) Spirit and Blessing: The Role of Flowers in Spirituality and the Human Environment, highlighting the importance of flowers in conveying the sincerity of the human heart in religious ceremonies, enrich spirituality, and deepen understanding of God's existence through religious symbols. Based on this, this research attempts to examine in depth the existence of flowers as a means of ritual through depiction or symbolization which allows humans to associate complex and abstract concepts such as God with something more concrete or visible, such as images, symbols, or rituals. This facilitates easier understanding and helps in forming an emotional, spiritual, or even intellectual bond with the concept of God.